The Influence of Product Quality, Price Fairness, and Brand Image on Shopee Image Purchase Decisions - Olivia novitasari simbolon; Nur Elfi Husda (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Skincare is the use of products aimed at taking care of skin health, improving appearance, and overcoming various skin problems. E-commerce such as Shopee plays an important role in making it easier to buy skincare products to buy products that suit your needs. Citra is a beauty product produced by Unilever Indonesia which already has popularity among the Indonesian people. Citra is known as a hand & body lotion product that uses natural ingredients. This study aims to determine the influence of product quality, price fairness, and brand image on the purchase decision of Citra products on Shopee. This research is a type of quantitative research with the nature of replication research. This study took samples using non-probability sampling techniques by purposive sampling. The research location was conducted in Batam City with a research period from March to August 2025. The sample size with the Lemeshow technique was 100 respondents with a population of buyers who made purchases of Citra products in Batam City through the Shopee application, therefore this type of population is an unknown type of population. The result of this research is that product quality has a positive influence on the purchase decision of Citra products on Shopee. Price reasonableness has a positive influence on the purchase decision of Citra products at Shopee. Brand image has a positive influence on the purchase decision of Citra products on Shopee. Product quality, price fairness and brand image have a positive effect along with the decision to purchase Citra products on Shopee.